2021
DOI: 10.1080/13696998.2021.1988282
|View full text |Cite
|
Sign up to set email alerts
|

Patient out-of-pocket costs for suspicious pulmonary nodule biopsy in lung cancer patients

Abstract: Aims: Dynamic changes in the payer landscape have resulted in increasing out-of-pocket costs (OOPC). Little is known about OOPC for patients undergoing biopsy for suspicious pulmonary nodules in the U.S. This study seeks to describe the spectrum of OOPC for diagnostic tissue sampling for suspicious pulmonary nodule with an ultimate diagnosis of lung cancer.Methods: Retrospective cohort study of adult patients with a primary lung cancer diagnosis and treatment who underwent diagnostic biopsy for suspicious pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Given that the Portuguese healthcare system consists of both public and private sectors, our study found that PHCs participants indicated diagnostic pathways for cancer patients linked to private institutions, which would imply out-of-pocket expenses for patients. These types of expenses have been thoroughly studied for treatments or medical care and until recent years no studies concerning out-of-pocket diagnostic were published [ 48 ]. Patients typically incur costs for laboratory and diagnostic services, with additional expenses for biopsies and complications [ 49 – 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the Portuguese healthcare system consists of both public and private sectors, our study found that PHCs participants indicated diagnostic pathways for cancer patients linked to private institutions, which would imply out-of-pocket expenses for patients. These types of expenses have been thoroughly studied for treatments or medical care and until recent years no studies concerning out-of-pocket diagnostic were published [ 48 ]. Patients typically incur costs for laboratory and diagnostic services, with additional expenses for biopsies and complications [ 49 – 51 ].…”
Section: Discussionmentioning
confidence: 99%